Cardiovascular Disease in Bangladesh: A Review (Bangladesh Heart Journal, 2017)
Like elsewhere, cardiovascular disease (CVD) is an increasingly important cause of morbidity and mortality in Bangladesh. Over the past few decades, because of epidemiological transition, the prevailing disease pattern in this country changed from predominantly communicable to predominantly non- communicable disease, CVD contributes to the latter a lot. Actually, CVD particularly coronary artery disease (CAD) is getting epidemic proportion day by day. Hypertension and heart failure are on the rise, whereas the prevalence of acute rheumatic fever is declining. However, despite some efforts, reliable data concerning various aspects of CVD is inadequate at present. The current prevalence of hypertension, CAD, rheumatic fever and rheumatic heart disease and stroke may be 20-25%, 4-6%,